THE ASSESMENT OF SPEAKING PRESENTATION BY THE FIRST SEMESTER IN ACADEMIC YEARS 2021/2022 FROM 2 UNIVERSITIES NON- ENGLISH MAYOR IN BANDUNG IN INDONESIA - Edi Purnama (Jurnal Sastra - Studi Ilmiah Sastra, 2024)
The aim of this research is not only to analyze of students’ presentation in learning English but also to analyze students’ presentation to enhance students’ speaking skill. The theory of Brown and Abewicakrama is used in this research. The descriptive study is used in this research. It took us one semester to take the data which were taken from 2 universities, 30 students from UNIKOM System Computer and 27 students from UNAS PASIM Informatics Management. They (57 Students) are guided and instructed to make a presentation of speaking in English 2 weeks before final test and they send their work to my email.  The highest average proportion is in the Lexical resource and range is 82 that it belongs to the Very Good (VG) and the second proportion is in Fluency and Coherence is 77 that it belongs to Good (G). The third proportion is in pronunciation is 68 and it belongs to satisfactory (S). The fourth is in grammatical range and accuracy is 65 it belongs to the satisfactory (S)